An updated review on low-temperature nanocomposites with a special focus on thermal management in buildings - John Paul, Nadakkal; K., Kadirgama; Mahendran, Samykano; Saidur, R.; Pandey, A. K.; Mohan, R. V. (Tech Science Press, 2022)
Buildings contribute to 33% of total global energy consumption, which corresponds to 38% of greenhouse gas emissions. Enhancing building’s energy efficiency remains predominant in mitigating global warming. Advancements in thermal energy storage (TES) techniques using phase change material (PCM) have gained much attention among researchers, primarily to minimize energy consumption and to promote the use of renewable energy sources. PCM technology stays as the most promising technology for developing high-performance and energy-efficient buildings. The major drawback of PCM is its poor thermal conductivity which limits its potential use which could be resolved by dispersing conductive nanofillers. The acquired database on synthesis routes, properties, and performance of nano-dispersed phase change materials (NDPCMs) with various techniques presented in the paper should deliver useful information in the production of NDPCMs with desirable characteristics mainly for building construction applications. An outline of contemporary developments and use of NDPCMs as TES medium is delivered. Finally, a brief discussion on challenges and the outlook was also made. In-depth research is needed to explore the fundamental mechanisms behind the enhanced thermal conductivity of NDPCM with nanofillers dispersion and also a thorough investigation on how these mechanisms drive improvement in building performance.